ADAM10 como biomarcadora de Transtorno Neurocognitivo Leve - Vatanabe, Izabela Pereira (2020)
Mild cognitive impairment (MCI), in the absence of dementia, and associated with physical frailty gave rise to the new concept called cognitive frailty. This new concept has also been considered as a subtype of frailty. Moreover, along with the aging process and its interaction with physical frailty, it accelerates the cycle of functional decline and results in poor quality of life and other negative outcomes in older adults. Previous studies have suggested that MCI may represent a condition that predates Alzheimer's disease (AD), based on the high conversion rate for it. With that in mind, the principal aim of this study was to evaluate whether the platelet and plasma levels of ADAM10 could act as biomarkers of the concomitant conditions of MCI and physical frailty, in order to support the new construct of cognitive frailty. The study was carried out with a population aged over 60 years old who were in the coverage of a family health center in the city of São Carlos-SP, Brazil. The subjects were properly assessed for cognition and physical frailty. Subsequently, biological samples were collected, analyzed and stored in a biorepository. The levels of platelet and plasma ADAM10 were analyzed using the Western blot technique in subjects with MCI, compared to subjects without the presence of cognitive impairments, both with and without the presence of frailty. The results indicate that ADAM10 levels are reduced in platelets and increased in plasma of older adults with MCI when compared to healthy controls, regardless of the condition of physical frailty. Based on the results obtained, this study raised the hypothesis that the plasma and soluble form of ADAM10 would be inactive, whereas the platelet form, anchored to the cell plasma membrane, would be active. Thus, we also aimed to assess whether the enzymatic activity of ADAM10 is dependent on its anchoring to the plasma membrane through the evaluation of the enzymatic activity of ADAM10 after the isolation of different fractions of SH-SY5Y neuroblastoma cells. Due to the worldwide pandemic scenario, the enzyme activity assay in cell fractions could not be completed, however a previous study carried out by this research group proved that ADAM10 found in plasma is enzymatically inactive, whereas the platelet form of the protein, was shown to be active, confirming our hypothesis that the reduced levels of active ADAM10 (60 kDa) are related to the condition of MCI, as well as the increased levels of inactive ADAM10 (50 kDa). Taken together, the results demonstrate that ADAM10 cannot be considered as a biomarker in conditions of cognitive frailty, but can act effectively as a low-cost, easy-access and low-invasive biomarker molecule for MCI. These results contribute to a better understanding of the biology of the molecule, as well as for the implantation of tools that promote the diagnosis of MCI. Furthermore, the evidence may guide the health teams to a more adequate planning, with the purpose of improving the quality of life of the older adults affected by this condition, and to direct therapeutic strategies and the prevention of injuries.